Parent-Child Interaction Therapy (PCIT): procedure and resources - Ruiz Olivares, Rosario; Valle Cobos, Susana (Pensando Psicología, 2025)
Parallel to the increase in child behavioural problems, intervention programmes aimed at parent training are becoming one of the most widely used tools in the treatment of this type of situation. The main objective of this article is to describe the Parent-Child Interaction Therapy (PCIT) procedure in detail with the idea of facilitating its dissemination and application by psychology professionals working with families with children with behavioural problems. For this purpose, an extensive bibliographic search has been carried out in order to gather all the available information about the procedure, as well as all the necessary instruments to be able to carry it out, respecting at all times the essential elements of the original therapy.
Keywords: PCIT; behavioural problems; intervention; families